Sistem Informasi Geografis Pelanggaran AKB dan PSBB Berbasis Android Menggunakan Metode Extreme Programming - Soni Ayi Purnama; Eva Susilawati (Masoem University, 2021)
The importance of providing accurate and real-time information is indispensable in today's era of rapid development of information technology. Along with technological developments, the condition of the Coronnavirus Disease 19 (Covid-19) pandemic is now a task to assist the government in reducing the chance of the spread of Covid-19, where this information technology is used as a means of supporting minimizing the chance of the spread of Covid-19. This study aims to assist the government and those who are authorized in Indonesia in society who violate the New Normal (AKB) and Large-Scale Social Restrictions (PSBB) regulations by utilizing information systems. The information system in question is an information technology-based information system that records and facilitates data processing of community actions during the PSBB and AKB by the government. The data method used in this research is observation, interview, and documentation. The system design method used is the Extreme Programming system design method. The results of this study are in the form of analysis and design of an Android-based Geographical Information System of New Normal and Large-Scale Social Restrictions (PSBB) using the Extreme Programming method.